Nutritional Infertility and Ameliorative Measures in Dairy Animals of Middle Gujarat - Dhami, A.J.; Patel, J.A.; Hadiya, K.K.; Parmar, S.C.; Chaudhari , D.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Fertility improvement camps were organized in different villages of middle Gujarat covering 1481 breedable cattle and buffaloes with the history of impaired fertility. The reproductive status of animals was ascertained through gynaeco-clinical examination per rectum. Blood sampling (n=305) was done from representative groups of animals to know the nutritional status. All non-infectious infertile animals were dewormed using either Inj. Ivermectin 100 mg s/c or bolus Fenbendazole + Ivermectin 3.0 g orally. Anestrus animals (n=265) were then nutritionally supplemented either with chelated area specific mineral mixture (ASMM, 50-60 g/d/h) or multi-minerals boli - one on alternate day, with and without bypass fat (75-80 g/d/h) for one month along with an advice to improve feeding level, estrus detection and timely breeding. Revisits were made after 2.5-3.0 months to check the reproductive status. The mean blood glucose concentrations were significantly lower (p<0.05), while total cholesterol and zinc levels were higher (p<0.05) in anestrus than in subestrus and/or repeat breeding cows and buffaloes. Moreover, the plasma total cholesterol levels in buffaloes were just one half to those of cows. Further, the plasma total protein, calcium, phosphorus, magnesium, iron, copper and cobalt concentrations were found to be non significantly higher in repeat breeders than in anestrus or subestrus cows and buffaloes. Calcium was deficient in some 20% animals and calcium: phosphorus ratio varied from 1:1 to 1.8:1 in animals under different areas of study indicating its role in causing infertility in dairy animals. Supplementation of ASMM, multi-mineral boli alone or in combination with bypass fat in pubertal /postpartum anestrus animals resulted in 34-56% estrus induction response and 33-50% conception rate, both being better with mineral plus bypass fat supplementation than minerals alone.